A comparative study of calorimetric methods to determine the crosslinking degree of the ethylene‐Co‐vinyl acetate polymer used as a photovoltaic encapsulant. Issue 11 (25th March 2017) - Ogier, Stéphane; Vidal, Chloé; Chapron, David; Bourson, Patrice; Royaud, Isabelle; Ponçot, Marc; Vite, Marion; Hidalgo, Manuel
ABSTRACT: EVA copolymer foils are widely used as encapsulants for photovoltaic (PV) cells in PV modules. These foils need to be crosslinked during module manufacturing, to enhance their properties. Accurate and reliable methods for the determination of their crosslinking degree are thus very important. In this work, two semi‐empirical calorimetric methods are considered and compared to a scientifically sound rheological method used as a reference. The main purpose of this work is to reveal the chemical and physical fundamentals on which the two calorimetric methods are based, to allow for a scientific understanding of their advantages, and limitations. For one of these calorimetric methods, the so‐called "Melt‐Freeze" method, we have sought for a deeper understanding of the underlying crystallization physics through the use of successive self‐nucleation and annealing experiments, which give access to the crystallite size distribution of EVA, and to the influence of crosslinking upon it. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 866–876 Abstract : EVA copolymer foils used as encapsulants for photovoltaic (PV) cells need to be crosslinked during module manufacturing. Accurate and reliable methods are crucial for the determination of their crosslinking degree. The main purpose of this work is to reveal the chemical and physical fundamentals on which two calorimetric methods used to determine the crosslinking degree of EVA are based. For one of these methods based upon crystallization, the authors have revealed the crystallite size distribution of the copolymer and the influence the degree of crosslinking has upon it.